(untitled) (VITAL, 2025)
Students from the Universidad Autónoma de Nayarit spent time at the Universidad Antonio Nariño in Bogotá. Their research focused on public health, working on topics such as adolescent health promotion, emotional intelligence, nutrition and exercise. Together they talk about their academic and cultural experience.